"Dynamic Strategic Monetary Policies and Coordination in Interdependent Economies: a Comment" - Crombrugghe, Alain De; Roubini, Nouriel; Sachs, Jeffrey (American Economic Review, 1991)
JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms